Equivalence trial of proposed denosumab biosimilar GP2411 and reference denosumab in postmenopausal osteoporosis: the ROSALIA study - Jeka, Sławomir; Dokoupilová, Eva; Kivitz, Alan; Żuchowski, Paweł; Vogg, Barbara; Krivtsova, Natalia; Sekhar, Susmit; Banerjee, Samik; Schwebig, Arnd; Poetzl, Johann; Body, Jean-Jacques; Eastell, Richard (Journal of bone and mineral research, 2024)
Denosumab is a monoclonal antibody used to reduce risk of fractures in osteoporosis. ROSALIA was a multicenter, double-blind, randomized, integrated phase I/phase III study comparing the efficacy, pharmacokinetics (PK), pharmacodynamics (PD), immunogenicity, and safety of proposed biosimilar denosumab GP2411 with reference denosumab (REF-DMAb) (Prolia®; Amgen). Postmenopausal women with osteoporosis were randomized 1:1 to 2 60-mg doses of GP2411 or REF-DMAb, one at study start and one at week 26. At week 52, the REF-DMAb group was re-randomized 1:1 to a third dose of REF-DMAb or switch to GP2411. The primary efficacy endpoint was percentage change from baseline (%CfB) in LS-BMD at week 52. Secondary efficacy endpoints were %CfB in LS-BMD, FN-BMD, and TH-BMD at weeks 26 and 78 (and week 52 for FN-BMD and TH-BMD). Primary PK and PD endpoints were the area under the serum concentration-time curve extrapolated to infinity and maximum drug serum concentration at week 26, and the area under the effect-time curve of the %CfB in serum CTX at week 26. Secondary PK and PD endpoints included drug serum concentrations and %CfB in serum CTX and P1NP during the study period. Similar efficacy was demonstrated at week 52, with 95% CIs of the difference in %CfB in LS-BMD between treatment groups fully contained within prespecified equivalence margins. Similarity in PK and PD was demonstrated at week 26. Immunogenicity was similar between groups and was not impacted by treatment switch. The rate of new vertebral fractures was comparable. Treatment-emergent adverse events were comparable between groups (63.6% [GP2411/GP2411]; 76.0% [REF-DMAb/REF-DMAb]; 76.6% [REF-DMAb/GP2411]). In conclusion, ROSALIA showed similar efficacy, PK and PD, and comparable safety and immunogenicity of GP2411 to REF-DMAb in postmenopausal osteoporosis.
Keywords: Biosimilar Pharmaceuticals; Female; Osteoporosis, Postmenopausal; ženské pohlaví; kostní denzita; Bone Density; clinical trials; bone modeling and remodeling: biochemical markers of bone turnover; lidé; dvojitá slepá metoda; Osteoporosis; denosumab; Bone Density Conservation Agents; biosimilární léčivé přípravky; Double-Blind Method; Denosumab; postmenopauzální osteoporóza; inhibitory kostní resorpce; osteoporóza; diseases and disorders of/related to bone: osteoporosis; Humans